French Peasants in Revolt : the Insurrection Of 1851. - Margadant, Ted W. (Princeton University Press, 2001)
The triumphant rise of Louis Napoleon Bonaparte over his Republican opponents has been the central theme of most narrative accounts of mid-nineteenth-century France, while resistance to the coup d'état generally has been neglected. By placing the insurrection of December 1851 in a broad perspective of socioeconomic and political development, Ted Margadant displays its full significance as a turning point in modern French history. He argues that, as the first expression of a new form of political participation on the part of the peasants, resistance to the coup was of greater importance than.